2018
DOI: 10.1371/journal.pone.0209484
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure prophylaxis for HIV prevention preferences among young adult African American men who have sex with men

Abstract: Pre-exposure prophylaxis (PrEP) is effective in preventing HIV infections among men who have sex with men (MSM). PrEP uptake and adherence remain low and product preferences are unknown, especially among young African American MSM who are most at-risk. We conducted 26 qualitative interviews from 2014–2016 among young adult HIV-negative African American MSM regarding PrEP product preferences in Missouri. While the pill and injectable were most liked of all modalities, about a quarter preferred rectal products o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
(65 reference statements)
1
34
1
Order By: Relevance
“…However, compared to MSM who preferred daily PrEP, a higher proportion of MSM who preferred on-demand PrEP during the online recruitment failed to attend on-site screening. Our finding of the higher preference for on-demand PrEP contradicts findings of studies from Belgium, the Netherlands, Australia and North America [8][9][10]26,27]; however, our finding accords with other findings from North America [28,29] and France [14]. It is important to note that the higher preference for daily reported in previous real-world studies (66% to 76.5%) (providing both daily and on-demand regimens of PrEP [8][9][10]) occurred among MSM who attended on-site screening.…”
Section: Discussioncontrasting
confidence: 90%
“…However, compared to MSM who preferred daily PrEP, a higher proportion of MSM who preferred on-demand PrEP during the online recruitment failed to attend on-site screening. Our finding of the higher preference for on-demand PrEP contradicts findings of studies from Belgium, the Netherlands, Australia and North America [8][9][10]26,27]; however, our finding accords with other findings from North America [28,29] and France [14]. It is important to note that the higher preference for daily reported in previous real-world studies (66% to 76.5%) (providing both daily and on-demand regimens of PrEP [8][9][10]) occurred among MSM who attended on-site screening.…”
Section: Discussioncontrasting
confidence: 90%
“…44 In populations at elevated risk of HIV infection, long-acting injectable regimens have also been hypothetically viewed favorably, although fear of needles and concerns about the duration of therapeutic efficacy may be barriers in some individuals. 8,9,[45][46][47][48] Again, retention rates, and quantitative and qualitative perspectives in direct headto-head comparisons with daily oral TDF/FTC in ongoing Phase 3 studies, will be very informative for implementation and scale-up should safety and efficacy be demonstrated.…”
Section: Acceptability Of Long-acting Prepmentioning
confidence: 99%
“…Furthermore, injectable technologies have repeatedly been viewed favorably among key popultions. 8,9 Rilpivirine, a non-nucleoside reverse trancriptase inhibitor (NNRTI), has been shown to have efficacy in HIV treatment when delivered as injectable anti-retroviral maintenance therapy in combination with cabotegravir in persons living with HIV (PLWH) who have not previously experienced virologic failure. 10 However, despite being safe, well-tolerated, and acceptable for PrEP in key populations, long-acting rilpivirine for PrEP has not moved forward into phase 3 studies due to storage and transportation limitations (cold chain required) and a low barrier to resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several classes of drugs that are being used in this regard. Several studies have shown that antiretroviral therapy has been effective in bringing down the viral load . However, the cost‐effectiveness of the PrEP as prevention of HIV infection remains an issue in regions with limited resources.…”
Section: Pharmacoeconomics Of Antiretroviral Agents In Prepmentioning
confidence: 99%
“…Long‐acting injectable was also a preferred type of therapy compared to tablets. Most subjects were happy to have daily oral tablets due to their unpredictable sexual episodes …”
Section: Pharmacoeconomics Of Antiretroviral Agents In Prepmentioning
confidence: 99%